Macromolecular selective flocculant derived from functionalized starch towards beneficiation of low-quality iron ore: Atomistic simulations and experimental studies. (August 2022) - Dey, Shaon; Patra, Abhay Shankar; Patra, Priyapratim; Saha, Biswajit; Mukherjee, A.K.; Pal, Sagar
Abstract: In this work, a selective flocculant (St-Meth-Co-PAM) has been developed through functionalization of starch (St). At first, starch methacrylate (St-Meth) has been synthesized by the simple esterification reaction of starch and methacrylic anhydride (MAh) and then a 3D network like formation has been developed by free radical polymerization among St-Meth molecules with simultaneous grafting of polyacrylamide chain on the St-Meth backbone. Several characterization techniques have been employed to check the development of the selective flocculant. From the selective flocculation study, it has been established that the material exhibits very good selective flocculation efficiency. From theoretical study, it has been confirmed that the material can form coordination with the hematite particles selectively. The synthesized material can be used in industrial purpose as it has been displayed very high settling speed rather than the conventional selective flocculant. Synopsis: During the beneficiation process of iron ore, a huge amount of extremely fine particles having size lower than 45 µm, called as slimes are produced. These slimes are generally deposited in large tailing ponds, which acquire large area and also it grabs immense volume of water that resulted in environmental pollution. This water cannot be used for another purpose. By virtue of this selective flocculation technique, the water can be reused and environmental pollution may be diminished. Graphical Abstract: ga1